The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.3389/fnins.2021.741651
|View full text |Cite
|
Sign up to set email alerts
|

Outer Retinal Layer Thickness Changes in White Matter Hyperintensity and Parkinson's Disease

Abstract: Purpose: To investigate the thickness changes of outer retinal layers in subjects with white matter hyperintensities (WMH) and Parkinson's Disease (PD).Methods: 56 eyes from 31 patients with WMH, 11 eyes from 6 PD patients, and 58 eyes from 32 healthy controls (HC) were enrolled in this study. A macular-centered scan was conducted on each participant using a spectral-domain optical coherence tomography (SD-OCT) device. After speckle noise reduction, a state-of-the-art deep learning method (i.e., a context enco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 44 publications
0
5
0
Order By: Relevance
“…Nerve fibers in the nasal quadrant arrive at the optic disk directly. Nerve fibers in the temporal quadrant are bounded by horizontal meridians, which, respectively, curve around the macular fovea and reach the optic disk ( 10 ). Among healthy individuals, the retinal thickness in the nasal quadrant is the thickest and the temporal quadrant is the thinnest ( 48 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Nerve fibers in the nasal quadrant arrive at the optic disk directly. Nerve fibers in the temporal quadrant are bounded by horizontal meridians, which, respectively, curve around the macular fovea and reach the optic disk ( 10 ). Among healthy individuals, the retinal thickness in the nasal quadrant is the thickest and the temporal quadrant is the thinnest ( 48 ).…”
Section: Discussionmentioning
confidence: 99%
“…Optical coherence tomography (OCT) is a non-invasive imaging technique based on low coherence interferometry that makes it possible to view high-resolution images of the retina in vivo . OCT system generates cross-sectional images of the retina that show the reflectivity information captured in depth by means of whiter or darker bands ( 10 ). RNFL is composed of ganglion cell axons that travel in bundles until the optic nerve.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, 31 patients (56 eyes) with WMH, six PD patients (11 eyes), and 32 healthy controls (58 eyes) were included. The results suggested that HFL + ONL, OS, and IZ + RPE layers were potentially associated with brain‐related diseases 77 . The parameters generated by the segmentation of retinal microvasculature and nerve layers offer a promising approach for the analysis of various neurodegenerative diseases.…”
Section: Application Of Ai Using Ocular Images For Systemic Diseases ...mentioning
confidence: 99%
“…The results suggested that HFL + ONL, OS, and IZ + RPE layers were potentially associated with brain-related diseases. 77 The parameters generated by the segmentation of retinal microvasculature and nerve layers offer a promising approach for the analysis of various neurodegenerative diseases. End-to-end DL models based on large datasets are increasingly popular in the analysis of neurological diseases.…”
Section: Neurological Diseasesmentioning
confidence: 99%